Social participation and exposure to tuberculosis education: a cross-sectional study of older (≥ 60 years) domestic migrants in China - Junping Liu; Chaojie Liu; Yu Cui; Zhixin Liu; Yajie Feng; Yanfu Wang; Li Guan; Wei Liu; Huanyu Zhang; Xinru Liu; Lin Wu; Zhaoyue Liu; et al. (BMC Public Health)
Abstract Background Older domestic migrants have a higher risk of infection of tuberculosis or reactivation of latent tuberculosis than other populations in China. This study aimed to assess the exposure level of older domestic migrants to tuberculosis education and its association with social participation. Methods Data were extracted from the 2017 China Migrants Dynamic Survey (CMDS). A total of 5,787 study participants over 60 years of age were eligible for this study. Multilevel logistic regression models were established to determine the association between social participation and exposure to tuberculosis education after adjustment for variations in sociodemographic characteristics of the participants and health resources available in their migration destinations. Propensity score matching (PSM) was conducted to precisely estimate the average treatment effect on the treated (ATT) of social participation on exposure to tuberculosis education. Results Only 28.5% of study participants reported exposure to tuberculosis education in various forms over the past year in their migration destination. Participation in social activities, both membership-based (aOR:1.68, 95% CI:1.46–1.94,) and non-membership-based (aOR:1.66, 95% CI:1.44–1.91) were associated with higher exposure to tuberculosis education after adjustment for variations in covariates. Those who resided in a province with higher prevalence of tuberculosis and higher health expenditure, established a local personal health record, were aware of the essential public health services, had a job, obtained higher levels of education, and self-rated good health were more likely to be exposed to tuberculosis education. The ATT of social participation reached 0.10, indicating an increase of 10% exposure to tuberculosis education in those with active social participation. Conclusions Low levels of exposure to tuberculosis education in older migrants are evident in China. Social participation is associated with higher exposure to tuberculosis education.